Comparative study of H2O2/PDS-based advanced oxidation process using Fe3O4 nanoparticles for Rhodamine B degradation: Mechanism, stability and applicability. (June 2022) - Liu, Dongdong; Tang, Yibo; Hao, Zhengkai; Chen, Dengqian; Li, Tianqi; Jiang, Lipeng; Tian, Bing; Yan, Cuiping; Luo, Yuan; Jia, Boyin
Abstract: In this work, we made a comparative study on the differences in the mechanism, stability and applicability of H2 O2 /Fe3 O4 and PDS/Fe3 O4 systems for Rhodamine B (RhB) degradation. The RhB degradation rate of H2 O2 /Fe3 O4 system could reach 71.5% at 60 min, and its primary mechanism was regarded as the heterogeneous catalysis occurring on Fe3 O4 surface. In this process, the newly formed Fe2 O3 covered the active sites on Fe3 O4 surface, hindering the continuous interaction between H2 O2 and Fe3 O4 . Alternatively, the RhB degradation rate of PDS/Fe3 O4 system could reach 98.5% at 60 min, and the homogeneous and heterogeneous catalysis were equally important. In this process, the formed S2 O8 2 ‐ promoted the cycle of iron species to produce a lot of OH and SO4 −, which significantly improved degradation performance. The RhB degradation pathway of two oxidation systems went through N-de-ethylation, chromophore cleavage, ring-opening and mineralization. After six cycles of degradation experiment, the RhB degradation rate of H2 O2 /Fe3 O4 and PDS/Fe3 O4 systems still reached 67.3% and 93.7%, and the corresponding mass loss of Fe3 O4 catalyst was only 2.68% and 4.5%, respectively. Next, the alkaline environment greatly hindered the catalytic decomposition of H2 O2 by Fe3 O4, thus the H2 O2 /Fe3 O4 system had a narrow pH application range (4.0–6.0), but PDS could be activated effectively by Fe3 O4 catalyst in a wide pH range (4.0–10.0). In addition, the PDS/Fe3 O4 system presented the stronger adaptability to actual water (including Cl ‐, CO3 2-, HCO3 - ) and multi-pollutant degradation (including methylene blue, acid orange 7, tetracycline and bisphenol A) than the H2 O2 /Fe3 O4 system. Finally, the two oxidation systems both effectively reduced the toxicity of pollutants and presented the exact cost. Highlights: Possible degradation mechanism and pathway of PDS/Fe3 O4 and H2 O2 /Fe3 O4 systems were proposed. Two oxidation systems effectively reduced the toxicity of pollutants and presented the low costs. PDS/Fe3 O4 system presented a strong adaptability to actual water and multi pollutant degradation. PDS/Fe3 O4 system showed the better degradation ability and stability than H2 O2 /Fe3 O4 system.